(γ, β)-PS-irresolute and (γ, β)-PS-continuous functions - Asaad, B.A.; Ahmad, Nazihah; Omar, Zurni (Academic Publications, Ltd., 2015)
This paper introduces some new types of functions called (γ, β)-PS-irresolute and (γ, β)-PS-continuous by using γ-PS-open sets in topological spaces (X, τ).From γ-PS-open and γ-PS-closed sets, some other types of γ-PS functions can also be defined. Moreover, some basic properties and preservation theorems of these functions are obtained. In addition, we investigate basic characterizations and properties of these γ-PS- functions. Finally, some compositions of these γ-PS- functions are given.